Juridicidade e efici??ncia econ??mica das imunidades tribut??rias eletr??nicas: livros, fonogramas e videogramas musicais - Bomtempo, Eug??nio Pacceli de Morais (2015)
This Dissertation addresses the legality and economic efficiency of tax immunities for e-books, music and video digital recordings. Based on the Kaldor-Hicks criterion, it is not possible to affirm whether these tax immunities are economically efficient, since the music and e-books markets are very concentrated. These Immunities may cause these segments become more concentrated and vertically integrated, increasing the risk of appropriation, by the majors, of part of the consumer surplus and part of the state revenues. The tax immunity of e-books can accelerate the disintegration of the printed books market. However, if the minimum extensive interpretation is applied for tax immunity of e-books the social costs may be mitigated. The musical tax immunity is phrased as a very open legal clause, so if the Supreme Court come up with an interpretation of the related laws according to the Federal Constitution, instead of broadening its meaning, its inefficiencies can be alleviated.